1980
DOI: 10.1068/a121235
|View full text |Cite
|
Sign up to set email alerts
|

Cognition and Shopping Choice: A Multidimensional Scaling Approach

Abstract: Interest in cognitive approaches has led to a need for means of ascertaining individual perceptions with a view to relating these to spatial behaviour. Yet such methods as the repertory grid, although invaluable for investigating individuals, make comparisons across a wider group difficult. The multidimensional scaling program PREFMAP possesses this facility through its assumption of a group cognitive space whose dimensions, while common to all, have different saliences for different individuals. This study te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

1982
1982
2002
2002

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Although this possibility is opened up by the method, no study has utilised it, previous MDS analyses having been restricted to studies of hazard perception (Odemerho, 1984), shopping behaviour (Spencer, 1980), and neighbourhood facilities, meanings, perceptions and preferences (Hourihan, 1979 ;Mueller, 1981) . The present work, drawn from the traditional city of Ibadan, explores the value of MDS in evaluating spatial inequalities from the viewpoint of the population .…”
Section: Discussionmentioning
confidence: 99%
“…Although this possibility is opened up by the method, no study has utilised it, previous MDS analyses having been restricted to studies of hazard perception (Odemerho, 1984), shopping behaviour (Spencer, 1980), and neighbourhood facilities, meanings, perceptions and preferences (Hourihan, 1979 ;Mueller, 1981) . The present work, drawn from the traditional city of Ibadan, explores the value of MDS in evaluating spatial inequalities from the viewpoint of the population .…”
Section: Discussionmentioning
confidence: 99%
“…The former group of factors appeared to be more important than the latter. Some subsequent studies have used the repertory grid (e.g., Hudson, 1974;Timmermans, van der Heijden, & Westerveld, 1982a) and MDS of similarity, dissimilarity, or preference ratings (e.g., Spencer, 1980). Results similar to those of Downs (1970) have been obtained with these techniques, which do not presuppose that attributes are specified in advance.…”
Section: Perception and Cognitive Representation Of Properties Of Placesmentioning
confidence: 99%
“…Some of the major work in this area has been undertaken by Spencer who suggested that dimensions associated with price, shopping center size, and location are important with regard to consumers images of retail environments [24]. In a subsequent study [25], he investigated how easily MDS data could be gathered in the field, and tested the degree to which measures of individual variation in cognition could be related to variations in spatial behavior. He indicated that while scaling is currently not adequately related to any underlying theory of cognition, it nonetheless offers a means by which individual and group cognitions of the retail environment can be related and analyzed with minimal bias.…”
mentioning
confidence: 98%